PENERAPAN ALGORITMA KLASIFIKASI NEAREST NEIGHBOR (K-NN) UNTUK MENDETEKSI PENYAKIT JANTUNG - MEI LESTARI (LPPM, 2014)
Data from WHO states that 7,3 million people die because of Heart Disease. Although Heart Disease is not contagious, this kind of disease is the number 1 disease causing death. Heart disease is also called as coroner disease. It happens when the blood drifting to the heart muscles stops so that it causes heart disorder (Rajkumar & Reena, September 2010). The application of Nearest Neighbor classification (K-NN) algorithm is expected to overcome the problems on the affectivity and accuracy in detecting heart disease. In this research, the K-NN with K = 9 is used on 100 patients of heart disease. The result revealed is that the accuracy is 70% and the AUC is 0.875 which belong to the good classification. Hence, K-NN algorithm can be used and applied in detecting heart disease. Keywords: Nearest Neighbor, Jantung, Algoritma, Akurasi.